Depression and physical multimorbidity during the adulthood. Cross-sectional associations. (30th September 2020) - Arias de la Torre, J; Ronaldson, A; Valderas, J M; JAlonso; Prina, M; Hatch, S; Rayner, L; Pickles, A; Hotopf, M; ADregan
Abstract: Introduction: The prevalence of depression and physical multimorbidity (pMM) might vary over the life course in a non-random fashion. The aims of our study were to: 1) assess the prevalence of depression and pMM over the life course; and 2) estimate changes in their pattern of association at different ages. Methods: Data from 13, 736 participants aged 26, 30, 34, 38, 42 and 46 years old of the British Child Study cohort was used. Individuals with information on current self-reported depression were selected as study sample. pMM (yes/no) caseness was defined as the coexistence of 2 or more self-reported physical conditions (e.g. asthma, diabetes, epilepsy). The prevalence of depression and pMM was calculated for each wave. To assess their relationship, prevalence ratios (PR) adjusted by gender, socioeconomic (e.g. educational level) and health-related variables (e.g. BMI and smoking status) and their 95% Confidence Intervals (95%CI) were obtained at each wave from multivariable Poisson models. Results: Prevalence of depression varied with age (10.0% at age 26, 7.8% at age 38 and 18.3% at age 46) as did prevalence of pMM (37% at age 26, 15.6% at age 34, and 20.2% at age 46). A non-linear trend in the prevalence both of depression and pMM was observed with a decrease from age 26 to age 38 (34 for pMM) followed by a consistent increment to age 46. In all ages depression was significantly associated with pMM the magnitude ranging from PR: 1.52 (95%CI 1.41-1.65) at age 26 to PR: 1.96 (95%CI 1.72-2.23) at age 38. Conclusions: There is consistent association between the prevalence of depression and pMM over different ages during adulthood. The non-linear pattern suggests differences in the type of conditions contributing to pMM at different ages (non-chronic in young adulthood vs chronic from middle adulthood). Further research on clusters and trajectories of different conditions over life course might be valuable to understand the association between depression and pMM. Key messages: There is consistent association between the prevalence of depression and pMM over different ages during adulthood. They could be differences in the type of conditions contributing to depression related pMM at different ages (non-chronic in young adulthood vs chronic from middle adulthood).